STUDI HALAL BERDASARKAN PENDEKATAN EPISTEMOLOGI - Masruhen, Mohmed Firdaus bin; Rahman, Arip; Ibrahim, Muhammad Yusuf (International Journal Mathla’ul Anwar of Halal Issues, 2023)
This research aims to conduct a study of the halal concept based on an epistemological approach. An epistemological approach is used to analyze the ways humans gain knowledge about the concept of halal in Islam, including through experience, religious authority, and scientific methods. This research will examine literature from main sources related to the concept of halal in Islam, as well as analyze various epistemological approaches used in understanding the concept of halal. It is hoped that the results of this research will provide a deeper understanding of the concept of halal and how humans gain knowledge about halal in the context of the Islamic religion. The research method used is literature study and qualitative analysis, as well as a compilation of literature from religious and philosophical experts. The conclusion of this research is that halal epistemology is the basis that explains how halal processes are applied both in the legal and social realms. This concept is understood from the results of studies conducted by Muslim scholars.